ANALYSIS OF POSTMODERNISM IN ORANG-ORANG BLOOMINGTON NOVEL BY BUDI DARMA - Muhsyanur, Muhsyanur (Universitas Andalas, 2019)
The purpose of this study was to describe aspects and characteristics of postmodernism in the novel Orang-orang Bloomington by Budi Darma. This study uses a descriptive approach. The method, which is collecting data, reading, and analyzing data. Based on the results of the study, the aspects of postmodernism were found, namely parody and camp, while the characteristics of postmodernism were found, namely the aspect of reducing admiration for science, capitalism, and technology , and shifting dominance.Â